Sport challenge activity in the midst of COVID-19 pandemic - Rachmad Wishnu Hidayat (Indonesian Nutrition Association, 2020)
The variation of exercise is important to avoid feeling bored and to keep the exercise motivation high. Although current condition is considered to be new normal with high number of new cases, it is recommend to exercise safely on location considered as low risk (e.g at home).